(untitled) (Journal of Plant Disease Sciences, 2023)
Soybean (Glycine max (L.) Merill) is the world’s most important oilseed crop, accounting for nearly half of total oilseed acreage and production. It is susceptible to diseases such as anthracnose, charcoal rot, bacterial blight, yellow mosaic virus, and others that pose a threat to soybean production. Root rot caused by Rhizoctonia bataticola is an important and major limiting factor for seed yield. Evaluation of four bioagents and seven different botanicals against Rhizoctonia bataticola were carried out in laboratory to determine their efficacy. Among the botanicals tested in laboratory at a concentration of 10% using the poisoned food technique, Azadirachta indica recorded the highest inhibition (62.96%) of R. bataticola mycelial growth and was significantly superior to the other treatments. This was followed by Oscimum sanctum (58.88%) and Milletia pinnata (58.88%). The dual culture technique was used to test the in vitro efficacy of bioagents against R. bataticola. Trichoderma asperellum inhibited growth the most (87.50%), followed by Trichoderma harzianum (81.38%).